Macrophage phenotype modulation by CXCL4 in atherosclerosis - Gleißner, Christian A. (Frontiers in physiology, 2012)
During atherogenesis, blood monocytes transmigrate into the subendothelial space and differentiate towards macrophages and foam cells. The major driver of this differentiation process is macrophage colony-stimulation factor (M-CSF). M-CSF-induced macrophages are important promoters of atherogenesis as demonstrated in M-CSF and M-CSF receptor knock out mice. However, M-CSF is not the only relevant promoter of macrophage differentiation. The platelet chemokine CXCL4 prevents monocyte apoptosis and promotes macrophage differentiation in vitro. It is secreted from activated platelets and has effects on various cell types relevant in atherogenesis. Knocking out the Pf4 gene coding for CXCL4 in Apoe-/- mice leads to reduced atherogenesis. Thus, it seems likely that CXC4-induced macrophages may have specific pro-atherogenic capacities. We have studied CXC4-induced differentiation of human macrophages using gene chips, systems biology and functional in vitro and ex vivo experiments. Our data indicate that CXCL4-induced macrophages are distinct from both their M-CSF-induced counterparts and other known macrophage polarizations like M1 macrophages (induced by LPS and interferon-gamma) or M2 macrophages (induced by interleukin-4). CXCL4-induced macrophages have distinct phenotypic and functional characteristics, e.g. the complete loss of the hemoglobin-haptoglobin (Hb-Hp) scavenger receptor CD163 which is necessary for effective hemoglobin clearance after plaque hemorrhage. Lack of CD163 is accompanied by the inability to upregulate the atheroprotective enzyme heme oxygenase-1 in response to Hb-Hp complexes. This review covers the current knowledge about CXCL4-induced macrophages, which based on their unique properties we have suggested to call these macrophages “M4”. CXCL4 may represent an important driver of macrophage heterogeneity within atherosclerotic lesions. Further dissecting its effects on macrophage differentiation may help to identify novel therapeutic targets.
Gesehen am 12.07.2018